Cover Picture: Preparation of Fluorescent Tubulin Binders (ChemPlusChem 3/2013). Issue 3 (11th March 2013) - Riva, Elena; Mattarella, Martin; Borrelli, Stella; Christodoulou, Michael S.; Cartelli, Daniele; Main, Marcus; Faulkner, Stephen; Sykes, Daniel; Cappelletti, Graziella; Snaith, John S.; Passarella, Daniele
<x xml:space="preserve">Abstract</x> The cover picture shows a lighthouse spreading its light on a stormy sea; this could be compared to the complexity of the biological role of tubulins and their involvement in cancer and neurodegenerative diseases. Just like a lighthouse, the microtubule structure could cast new light on live cell imaging studies if it incorporates fluorescent tubulin units. The compounds obtained by conjugation of tubulin binders with fluorescent probe molecules act as a bulb that can secure a direct assay to evidence the tubulin/microtubules network and offer a solution to overcome the invasive techniques of transfection or microinjection but also time‐consuming immunofluorescence staining. A full account can be found in the Full Paper by D. Passarella and co‐workers on page 222 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>